Optimizing PhET Use in Rwandan Mathematics and Sciences Teaching - Niyibizi, Onesme (Universitas Terbuka, 2024)
This qualitative study examined the effectiveness of professional development programs for mathematics and sciences teachers in four public secondary schools within Gasabo District, Rwanda. The primary focus was to evaluate how these programs enhance teachers' ability to integrate Physics Education Technology (PhET) simulations into their classrooms. The research involved 42 participants. Data collection methods included in-depth interviews, classroom observations, and document analysis. Findings revealed that professional development programs significantly improved teachers' confidence and proficiency in using PhET simulations, resulting in more engaging and effective mathematics and science education. The study highlighted the importance of adapted professional development to enhance teachers' use of technology in the classroom, with potential implications for improving mathematics and science education in the region.